Experimental investigation and FEA of AlMg3-stiffened rectangular plate subjected to concentrated load - Midhat Hasan, Mohammed; Yaseen Abbood, Mazin (Iraqi Journal of Civil Engineering, 2013)
In this paper, AlMg3-plates are studied through experimental and numerical using finite element representation under concentrated load at the center point. The plates of (300- × 200 mm) are clamped at the shorter ends and strengthened longitudinally by one rib at the centerline and two at different spans. the stiffened plates were modeled using a 3-D 10-node tetrahedral element with a non dimensional analysis. The models were validated using the results of tests on full-size stiffened plate specimens and were subsequently used to perform the study of the parameters presented in this paper. The parameters investigated are: the maximum stress, deflection of the plate and the position of ribs. Effect of the investigated parameters on the concentrated load strength were studied within elastic range. FEA give closer results with those of experimental and these results show that the use of two parallel ribs with a 40-mm span improves the strength of the plate. Due to these results, further investigation is presented to show the optimum thickness of the ribs at the best span.